2014
DOI: 10.1128/genomea.01267-13
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequences of Three Species D Adenoviruses Isolated from AIDS Patients

Abstract: HAdVD23 and two novel adenoviruses, HAdVD60a and HAdVD62, isolated from feces of AIDS patients in Manchester, United Kingdom, have been sequenced. The HAdVD60a genome lacks the penton arginine-glycine-aspartic acid (RGD) motif and differs from HAdVD60 by a recombinant E3 region. HAdVD62 has penton, hexon, and fiber regions not previously found in other adenoviruses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Human adenoviruses (HAdV) are associated in humans with a broad spectrum of clinical diseases, such as acute respiratory disease (ARD), community-acquired pneumonia (CAP), as well as conjunctivitis, gastrointestinal, opportunistic infections in immune-deficient individuals, and possibly, obesity ( Dingle and Langmuir , 1968 ; Chu and Pavan-Langston, 1979 ; Wood, 1988 ; Dhurandhar et al, 1992 ; Kojaoghlanian et al, 2003 ; Hakim and Tleyjeh, 2008 ). Since the first HAdV isolate was found in 1953 ( Hilleman et al, 1953 ; Rowe et al, 1953 ), more than 80 HAdV genotypes have been identified and classified into seven species (A to G) using the whole-genome sequence as the typing standard 1 ( Jones et al, 2007 ; Ishiko et al, 2008 ; Walsh et al, 2009 , 2010 , 2011 ; Liu et al, 2011 , 2012 ; Matsushima et al, 2011 , 2012 , 2013 ; Robinson et al, 2011 , 2013b ; Seto et al, 2011 ; Dehghan et al, 2012 ; Singh et al, 2012 , 2013 ; Zhou et al, 2012 ; Alissa Alkhalaf et al, 2014 ; Hage et al, 2015 ; Hashimoto et al, 2018 ). HAdV species B are further divided into subspecies B1 (HAdV-B3, -B7, -B16, -B21, and -B50) and B2 (HAdV-B11, -B14, -B34, -B35, and -B55) according to their restriction enzyme digestion patterns ( Wadell et al, 1980 ).…”
Section: Introductionmentioning
confidence: 99%
“…Human adenoviruses (HAdV) are associated in humans with a broad spectrum of clinical diseases, such as acute respiratory disease (ARD), community-acquired pneumonia (CAP), as well as conjunctivitis, gastrointestinal, opportunistic infections in immune-deficient individuals, and possibly, obesity ( Dingle and Langmuir , 1968 ; Chu and Pavan-Langston, 1979 ; Wood, 1988 ; Dhurandhar et al, 1992 ; Kojaoghlanian et al, 2003 ; Hakim and Tleyjeh, 2008 ). Since the first HAdV isolate was found in 1953 ( Hilleman et al, 1953 ; Rowe et al, 1953 ), more than 80 HAdV genotypes have been identified and classified into seven species (A to G) using the whole-genome sequence as the typing standard 1 ( Jones et al, 2007 ; Ishiko et al, 2008 ; Walsh et al, 2009 , 2010 , 2011 ; Liu et al, 2011 , 2012 ; Matsushima et al, 2011 , 2012 , 2013 ; Robinson et al, 2011 , 2013b ; Seto et al, 2011 ; Dehghan et al, 2012 ; Singh et al, 2012 , 2013 ; Zhou et al, 2012 ; Alissa Alkhalaf et al, 2014 ; Hage et al, 2015 ; Hashimoto et al, 2018 ). HAdV species B are further divided into subspecies B1 (HAdV-B3, -B7, -B16, -B21, and -B50) and B2 (HAdV-B11, -B14, -B34, -B35, and -B55) according to their restriction enzyme digestion patterns ( Wadell et al, 1980 ).…”
Section: Introductionmentioning
confidence: 99%
“… estimated the 1‐year actuarial risk of adenovirus infection in persons infected with HIV to be 28%. Multiple, previously unrecognized HAdV‐Ds were discovered during the global AIDS epidemic, including HAdV‐D43‐51, D58, D59, D62, and D75 . In addition, numerous reports detail previously identified viruses that were found to infect AIDs patients .…”
Section: Viral Persistence Host Immune Suppression and The Evolutiomentioning
confidence: 99%
“…HAdV recombination continuously happens between strains of the same species ( 6 ). Mutations in hexon, fiber, and penton base proteins result in new strains of the adenovirus ( 7 ). The regions of loop1 and 2, and hypervariable regions 1–7 of hexon gene have shown to be highly susceptible to homologous recombination among HAdV-D ( 8 ).…”
Section: Introductionmentioning
confidence: 99%